Property development - Wilkinson, Sara; Reed, Richard; Cadman, David (London ; Routledge, 2008)
'Property Development' gives the reader a complete overview of the development process. It is intended as an introductory text for students and others coming to the property development process for the first time, and case studies are included to provide real illustrations of aspects of this process.
Rev. ed. of: Property development / David Cadman and Rosalyn Topping. 4th ed. 1995.
Keywords: Real estate development; Real estate development